Case report of optic atrophy in Dentatorubropallidoluysian Atrophy (DRPLA). Issue 1 (December 2015) - Silver, Michael; Sethi, Kapil; Mehta, Shyamal; Nichols, Fenwick; Morgan, John
Abstract Background Dentatorubropallidoluysian atrophy (DRPLA) is a rare autosomal dominant neurodegenerative disease that is associated with numerous movement disorders. Ocular problems also occur with DRPLA with reports of corneal endothelial degeneration in some patients living with the disease. We report a new visual problem associated with DRPLA, optic atrophy. Case presentation A 47 year-old man presented complaining of progressive visual loss associated with optic atrophy on ophthalmological evaluation. He gradually developed a progressive ataxia with dystonia. Brain MRI revealed a diffuse leukoencephalopathy. Genetic analysis revealed 62 CAG repeats in one allele of the DRPLA gene and he was diagnosed with DRPLA. Conclusion Optic atrophy should be included in the clinical spectrum of DRPLA.